الأساليب السلوكية في تعليم اللغة العربية في السنة السابعة بالمرحلة المتوسطة بمعهد بناء مدني ببوجور - Saipuddin Saipuddin; Nabil Ahmed Tarmom; Abdul Hayyie al Kattani; Ulil Amri Syafri (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2022)
Learning Arabic according to the behavioristic view is learning that prioritizes mastery of listening and speaking skills, after mastering these two skills, the next skill that must be taught is reading and writing skills. Language skills according to this view are the same as mastery of other behavioral skills such as playing ball, driving a car, and so on, which requires learning, practice, and simulation, and is very dependent on the stimulus and response process, as well as reinforcement. The method used in this study is a qualitative research method with a field research approach. The results of this study are that there are behavioristic ways in teaching Arabic at the junior high school level at Ma'had Bina Madani Bogor, including the formation of an Arabic-speaking environment in the classroom, preparing students, providing learning media that can shape students' language behavior, using direct methods, using the audio lingual method, overdoing it in practice on different aspects of sound between Arabic and Indonesian, explaining the meaning of vocabulary by relating it to pictures, gestures, or example movements, explaining the meaning of vocabulary by connecting it with plurals, equations, or differences, learning Arabic grammatical rules through conversation, familiarizing students with listening to Arabic voices, providing listening exercises, getting students used to speaking in Arabic, providing speaking exercises in Arabic, and providing positive or negative reinforcement. negative.